Dimerization of the SP1 Region of HIV-1 Gag Induces a Helical Conformation and Association into Helical Bundles: Implications for Particle Assembly - Datta, Siddhartha A. K. (J Virol, 2016)
HIV-1 immature particle (virus-like particle [VLP]) assembly is mediated largely by interactions between the capsid (CA) domains of Gag molecules but is facilitated by binding of the nucleocapsid (NC) domain to nucleic acid. We previously investigated the role of SP1, a “spacer” between CA and NC, in VLP assembly. We found that small changes in SP1 drastically disrupt assembly and that a peptide representing the sequence around the CA-SP1 junction is helical at high but not low concentrations. We suggested that by virtue of such a concentration-dependent change, this region could act as a molecular switch to activate HIV-1 Gag for VLP assembly. A leucine zipper domain can replace NC in Gag and still lead to the efficient assembly of VLPs. We find that SP1 mutants also disrupt assembly by these Gag-Zip proteins and have now studied a small fragment of this Gag-Zip protein, i.e., the CA-SP1 junction region fused to a leucine zipper. Dimerization of the zipper places SP1 at a high local concentration, even at low total concentrations. In this context, the CA-SP1 junction region spontaneously adopts a helical conformation, and the proteins associate into tetramers. Tetramerization requires residues from both CA and SP1. The data suggest that once this region becomes helical, its propensity to self-associate could contribute to Gag-Gag interactions and thus to particle assembly. There is complete congruence between CA/SP1 sequences that promote tetramerization when fused to zippers and those that permit the proper assembly of full-length Gag; thus, equivalent interactions apparently participate in VLP assembly and in SP1-Zip tetramerization. IMPORTANCE Assembly of HIV-1 Gag into virus-like particles (VLPs) appears to require an interaction with nucleic acid, but replacement of its principal nucleic acid-binding domain with a dimerizing leucine zipper domain leads to the assembly of RNA-free VLPs. It has not been clear how dimerization triggers assembly. Results here show that the SP1 region spontaneously switches to a helical state when fused to a leucine zipper and that these helical molecules further associate into tetramers, mediated by interactions between hydrophobic faces of the helices. Thus, the correct juxtaposition of the SP1 region makes it “association competent.” Residues from both capsid and SP1 contribute to tetramerization, while mutations disrupting proper assembly in Gag also prevent tetramerization. Thus, this region is part of an associating interface within Gag, and its intermolecular interactions evidently help stabilize the immature Gag lattice. These interactions are disrupted by proteolysis of the CA-SP1 junction during virus maturation.